Cardiovascular health control in the family health strategy - Tavares, Gilberto Andrade; Ribeiro, Joathan Borges; Almeida-Santos, Marcos Antonio; Sousa, Antônio Carlos Sobral; Barreto-Filho, José Augusto Soares (Frontiers in Cardiovascular Medicine, 2022)
Introduction The Unified Health System regulates Brazilian public health care and the Family Health Strategy (FHS) handles epidemiological surveillance and control of risk factors for cardiovascular diseases. In 2010, the American Heart Association (AHA) proposed the evaluation of seven metrics with the aim of monitoring cardiovascular health (CVH). However, the results of the FHS regarding the CVH of the Brazilian population are not known. Objective Evaluate the control of CVH among adult patients assisted by the FHS in the municipality of Aracaju, Sergipe, Brazil. Material and Methods A cross-sectional study was conducted using the seven metrics recommended by the AHA to evaluate CVH among patients treated by the FHS. The population in the municipality of Aracaju is 571,149 inhabitants, with 394,267 > 20 years of age. Thus, it was admitted that in a simple random sample, sampling error of 5% with 95% CI, 329 individuals would be needed. Results Among 400 patients, only 32.5% had controlled CVH. The adjusted multivariate analysis found that being female (aOR 2.07 IC 1.20-3.60, p 0.006) under 45 years old (aOR 1.61 IC1.15-2.28, p 0.006) and with the habit of share health guidance from family members and neighbors (aOR 1.28 IC 1.15-2.28, p 0.040) were associated with control of CVH. On the other hand, those ones who had a greater number of children (aOR 0.91 IC 0.84-0.95, p 0.020) were associated with less control of CVH. Conclusions The study showed that only 32.5% of patients have controlled CVH. Being a woman, young and following health guidance from family members and neighbors positively influenced the control of CVH. More children reduced control of these metrics.